Vermicomposting as a potential strategy for microplastic reduction in organic waste: mini review - Ardin Abdul Gafur, Muzna; Gupta, Puneet Kumar; Iswahyudi, Iswahyudi; Setyobudi, Roy Hendroko (Institute for Research and Community Service (LPPM), Universitas Islam Madura, Indonesia, 2025)
Microplastics have emerged as one of the most concerning pollutants increasingly detected in organic waste streams, including household waste, agricultural residues, and fecal sludge. The presence of microplastics in recycled waste products, such as compost, introduces a new threat to soil quality and food safety. One promising biological approach for mitigating microplastic contamination is vermicomposting a process that involves the decomposition of organic waste facilitated by earthworms. This review aims to evaluate the potential of vermicomposting in reducing microplastic contamination, as well as its effects on earthworm health and the quality of the resulting compost. The methodology involved an extensive literature review of articles published in Scopus-indexedjournals between 2020 and 2025. The review findings indicate that earthworm activity can contribute to the physical fragmentation of microplastics, stimulate microbial degradation within the gut, and potentially alter the chemical structures of specific polymers, such as polypropylene (PP) and high-density polyethylene (HDPE). However, the presence of microplastics also exerts negative effects, including the induction of oxidative stress, reduced earthworm biomass, decreased survival rates, and alterations in compost quality, particularly the carbon-to-nitrogen (C/N) ratio. These findings suggest that although vermicomposting is not yet fully capable of completely degrading microplastics, it holds potential as an early-stage technology for managing organic waste contaminated with microplastics. Further research is required to gain a deeper understanding of the underlying biological mechanisms and to develop more efficient and safe integrated vermicomposting systems for sustainable agricultural practices.